1993
DOI: 10.1159/000204502
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocyte, Erythroid and Granulocyte-Macrophage Colony Formation in Myelodysplastic Syndromes

Abstract: Bone marrow progenitor cell assays of three cell lineages, i.e., colony-forming unit megakaryocytes (CFU-Meg), burst-forming unit erythrocytes (BFU-E) and colony-forming unit granulocyte-macrophages (CFU-GM), were performed for 21 patients with myelodysplastic syndromes (MDS). Markedly reduced or absent colony formation was found in 67% of the patients for CFU-Meg and all patients except 2 with refractory anemia (RA) for BFU-E. Abnormal CFU-GM colony formation was found in only 5 of 12 patients with RA and RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
2
13
1
2
Order By: Relevance
“…Most reports, using short-term colony cultures, have shown that there is no correlation between the colony growth and the specific bone marrow karyotypes except for 5q− syndrome. 41 Furthermore, our results failed to detect significant differences in secondary CFC numbers between the patients with or without abnormal cytogenetics in the RA + RARS group, while in the RAEB + RAEB-T group such differences were present. This finding suggested that chromosome abnormalities can (at least indirectly) affect secondary CFC numbers in RAEB + RAEB-T, eg during leukemic transformation.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Most reports, using short-term colony cultures, have shown that there is no correlation between the colony growth and the specific bone marrow karyotypes except for 5q− syndrome. 41 Furthermore, our results failed to detect significant differences in secondary CFC numbers between the patients with or without abnormal cytogenetics in the RA + RARS group, while in the RAEB + RAEB-T group such differences were present. This finding suggested that chromosome abnormalities can (at least indirectly) affect secondary CFC numbers in RAEB + RAEB-T, eg during leukemic transformation.…”
Section: Discussioncontrasting
confidence: 78%
“…39 In agreement with our results of LTBMC, there were no clear differences in the colony growth between the FAB subtypes, although patients with RA and RARS generally show normal CFU-GM colony formation. 40,41 However, we demonstrated normal secondary colony formation in only 19.4% (seven of 36) of RA and RARS patients, suggesting that this parameter is more sensitive and perhaps reflects more precisely the defect of hematopoietic stem cell compartment than the conventional culture method. While deficiency in the growth and output of clonogenic cells has been previously shown to be greatly reduced in the majority of MDS bone marrow, no significant abnormalities in the stromal compartment have been demonstrated.…”
Section: Discussionmentioning
confidence: 66%
“…The mean CFUmeg number of healthy controls by this method was three or four times the values obtained previously with the fibrin clot culture system. [17][18][19][20] Although the new system seems better than previous methods of culturing CFU-meg, it only provides Leukemia the number of CFU-meg per BMLD cell for different types of bone marrow cells in different diseases. We need to be cautious when interpreting the data as it does not provide the absolute number of CFU-meg per constant number of BM cells.…”
Section: Discussionmentioning
confidence: 99%
“…27 Previous studies have demonstrated that CFU-meg numbers in MDS were normal in some patients, but decreased in most. 18,28 In addition, the number of megakaryocytes per colony was also reported to be reduced. 29 Consistent with these studies, two-thirds of the patients, group III in our study, showed reduced numbers of CFU-meg; most of them were small colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of hypotheses based upon the preleukemia paradigm have been explored [24][25][26][27] The absence of a coherent mechanistic explanation for these disorders has prompted us to reexamine the assumptions behind current models of MDS [21][22][23]. The marrow of MDS patients consistently demonstrates decreased hematopoietic progenitor colonies [29][30][31][32][33][34] as well as enhanced levels of apoptosis [35][36][37][38][39][40][41][42][43][44][45][46][47]. These two findings are felt to explain the paradox of a hypercellular bone marrow with profound peripheral cytopenias observed in MDS patients [48] and suggests that a propensity to apoptosis is responsible for the initiation of these disorders.…”
mentioning
confidence: 99%